Screening the plants of Orchidaceae Juss. family for the antioxidant properties of the extracts of leaves - Cherevchenko, T.M.; Ivannikov, R.V.; Laguta, I.V.; Buyun, L.I.; Stavinskaya , О.N.; Dzyuba, О.I. (Reports of the National Academy of Sciences of Ukraine, 2016)
Using plants grown ex situ and in vitro, the extracts from leaves of seventeen species of Orchidaceae Juss. family are prepared. Antioxidant activity of the extracts is studied, and the content of flavonoids in the extracts is estimated. The extracts from leaves of ten species are found to possess high antioxidant properties and/or a high content of flavonoids that makes them potentially interesting raw materials for the production of effective antioxidants of nature originals. Five of these ten species had a high content of bioactive compounds, being cultivated in vitro; these plants may be used in biotechnological processes of antioxidants/flavonoids production.